Optimizing Early Childhood Education Student Development Data Governance Through the Implementation of the EduPrima Information System with Learning Analytics - Suci Sri Utami Sutjipto; Septian Cahyadi; Bambang Hengky Rainanto; Rahma Djati Kusuma; Jemy Arieswanto (Universitas Ibn Khaldun, 2026)
Early childhood education has a strategic role in the foundation of child development, but SS Schools in Bogor still face administrative obstacles due to inefficient manual recording systems, prone to data loss, and hindering holistic monitoring of child development. Key problems include unstructured data management and the absence of analytical tools to support teachers' instructional decisions. This program implements a web-based EduPrima application that provides integrated data management and Learning Analytics features through the stages of socialization, system development, technical training, and intensive mentoring. As a result, administrative digitization improves operational efficiency and provides objective supporting data, so that institutional governance becomes more accountable and transparent without replacing the primary pedagogical role of teachers.